Penggunaan Model Problem Based Learning Untuk Meningkatkan Kompetensi Pengetahuan dan Kemampuan Berpikir Kreatif Siswa SMP IT Darul Hikmah Pasaman Barat - Syamina, Syamina; N, Annisa; Nurhaliza, Putri; Agustina, Nelmi (Universitas Negeri Padang, 2021)
The 21st century continues to experience developments, including in the world of education. The development of the 21st century in the world of education poses more complex challenges. The most important thing that students must have in the 21st century is a knowledge base and deep understanding and develop various other abilities. One of the abilities that students must have in the 21st century is the ability to think creatively, not least in learning science. Science learning is related to events that occur in nature. Therefore, a strategy is needed for teachers to build students' creative thinking skills so that students can gain the right knowledge. One way that can be used to improve students' creative thinking skills is to use the Problem Based Learning (PBL) model. Based on research that has been conducted in class VIII SMP IT Darul Hikmah, it is known that the PBL model is effective in improving knowledge competence and students' creative thinking abilities